Heteroatom‐interchanged isomers of lissoclinamide 5: Copper(II) complexation, halide binding, and biological activity - Xie, Sida; Kerscher, Marion; Comba, Peter (European journal of organic chemistry, 2018)
Cyclic peptides found in nature are often proposed as biological metal chelators owing to their cavitand architectures. This theory was probed by synthesizing and evaluating the physical and biological properties of heteroatom‐interchanged variants. A comprehensive study reaffirmed that small structural changes induce dramatic effects in complexation, halide binding, and biological activity.